2015
DOI: 10.1016/j.jmb.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 and Hsp90 of E. coli Directly Interact for Collaboration in Protein Remodeling

Abstract: Hsp90 is a highly conserved molecular chaperone that remodels hundreds of client proteins, many involved in the progression of cancer and other diseases. It functions with the Hsp70 chaperone and numerous cochaperones. The bacterial Hsp90 functions with an Hsp70 chaperone, DnaK, but is independent of Hsp90 cochaperones. We explored the collaboration between E. coli Hsp90 and DnaK and found that the two chaperones form a complex that is stabilized by client protein binding. A J-domain protein, CbpA, facilitates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
105
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 55 publications
18
105
0
Order By: Relevance
“…In addition to ATP, TRAP1-dependent protein folding also requires the functional cooperation of the mitochondrial Hsp70 system. The latter supports a direct physical interaction, as was recently reported for cytosolic Hsp90 chaperones (5)(6)(7)50), and opens up new avenues for drug development by targeting the specific interaction between mitochondrial chaperones.…”
Section: Discussionsupporting
confidence: 83%
“…In addition to ATP, TRAP1-dependent protein folding also requires the functional cooperation of the mitochondrial Hsp70 system. The latter supports a direct physical interaction, as was recently reported for cytosolic Hsp90 chaperones (5)(6)(7)50), and opens up new avenues for drug development by targeting the specific interaction between mitochondrial chaperones.…”
Section: Discussionsupporting
confidence: 83%
“…We previously showed that E. coli DnaK collaborates with Hsp90 Ec in protein reactivation and that the two chaperones physically interact through a region in the middle domain of Hsp90 Ec [23, 30]. To elucidate the region of DnaK essential for binding Hsp90 Ec , we used molecular docking to predict potential interactions between the two chaperones.…”
Section: Resultsmentioning
confidence: 99%
“…GrpE, the bacterial NEF stimulates reactivation, but is not essential [23]. ATP hydrolysis and client binding by both chaperones is essential for reactivation [30]. Moreover, bacterial Hsp90 physically interacts with DnaK in vivo and in vitro [29, 30] through a region identified on the M-domain of Hsp90 Ec [30].…”
Section: Introductionmentioning
confidence: 99%
“…Within the chaperone network, many of the major chaperones make physical interactions with each other. For example, the prokaryotic orthologs of Hsp70 and Hsp90 directly bind to each other [9; 10], as do the orthologs of Hsp70 and Hsp110 [11]. In mammals, Hsp70s are physically linked to the Hsp90s, but through the scaffolding protein, HOP (Hsc70-Hsp90 organizing factor).…”
Section: Introductionmentioning
confidence: 99%